PENGGUNAAN METODE PEMBERIAN TUGAS DALAM PENGEMBANGAN KREATIVITAS DI TK KARTIKA XVII-03 PONTIANAK UTARA - Fitriani, Eka; Marmawi, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the fact that despite already using task giving method, but in preparing the instrument and materials which will be used, not all teachers can develop the children’s creativity. The general purpose of this research is to describe the use of task giving method in developing the creativity of children ages 5 to 6 in TK Kartika XVII-03 North Pontianak. The data sources consist of 1 teacher and 15 students from class B2. The conclusion of this research is that the teacher had used the task giving method effectively by preparing the instrument and materials which would be used and by guiding the children well. The learning results were also satisfying because after the fifth meeting, there was no question raised by the children. For the teacher, it is hoped that the children are paid attention to more so that they do not play on their own. In addition, it would be better if the media used were more varied so that the children would not be bored. Lastly, it is necessary to add more educational toys to boost the children’s learning and creativity. Keywords: Creativity, Task Giving Method,